A conceptual model of the drivers and outcomes of mobile CRM application adoption. Issue 1 (14th March 2016) - Rodriguez, Michael; Trainor, Kevin
Abstract : Purpose: – Many organizations still struggle with sales force technology implementation because of low user adoption rates. The ubiquity of mobile computing devices, such as smartphones and tablets, and the proliferation of mobile customer relationship management (mCRM) applications, may lead to increased CRM adoption and higher returns on CRM technology investments. The purpose of this study is to attempt to extend the current literature by developing a model of mCRM antecedents and outcomes by incorporating the idiosyncratic mCRM characteristics that have not yet been examined in the sales technology literature. Design/methodology/approach: – This research utilizes the technology acceptance model and the technology-to-performance chain as the foundation of a conceptual model of the drivers and outcomes of mCRM adoption. Findings: – This conceptual study provides several contributions to both the sales technology literature and to practitioners within sales organizations. The proposed conceptual model outlines the benefits of providing mCRM capabilities to sales professionals. These benefits include increased productivity, sales activity and collaboration among both internal stakeholders (management and peers) and external stakeholders (prospects and customers). Originality/value: – Despite the increased use of mobile applications in sales, research on this particular form of technology is limited, and sales researchers have yet to examine mCRM or its relationship to sales performance. Therefore, the purpose of this research is to forward a conceptual model that allows researchers to explore the drivers of mCRM use and how mCRM influences individual and organizational-level outcomes.